An Industrial systems design study on Casa Mikael International, Inc. - Difuntorum, Lee Michael D.; Gabaon, Jennifer Frances M.; Magno, Cheryl Omega M.; Paynor, Edgar Kevin P. (College of Engineering, 2003)
Casa Mikael International, Inc., which started in 1993, is an exporter of polyresin ? based decorative items primarily to the US and selected European countries. Producing high quality and intricate designed decors as its competitive priorities, the company boasts of offering the market with over 10,000 designs. Its products are categorized by function and by themes (e.g. Christmas, Easter, Fall and Everyday Themes). A documentation of its current systems was conducted in terms of its financial status, market position, technical capabilities and environmental analysis. Through the company's financial statements and reports for years 1996 to 2011, a sudden increase in sales (by 50.65%) was seen from year 199 to 2000. Export trade grew by 8% from 2000 to 2001. Financial ratios were computed to measure the company's profitability, liquidity, cash solvency, and growth over time. It was found out that CMI has low current and quick ratios, meaning the company's credit liabilities are larger than its current assets, thus denying CMI of a good credit risk because of its difficulty to meet short and long term obligations. In the market review, demand and supply analyses were performed on analogous products, specifically Easter and Christmas ornaments excluding light fittings to aid in assessing CMI's possibilities to expand to wider horizons. In 2001, the company captured 10.85% of the demand, which is based on Philippine exports of Christmas and Easter articles. Market analysis further indicates a significant opportunity for the company to expand. Moreover, different environmental impacts of the company's processes and elements were also evaluated and various solutions proposed. After analyzing the current business strategies and operations, it is inherent to say that the company would need to reevaluate its strategic and operational goals. A SWOT analysis was conducted to focus on major problems that contribute inefficiencies in production, marketing and sales. Streamline Diagnosis Diagram and various tools for problem analyses were performed to identify specific problems at both the strategic and operational level. Consequently, the major concern of the company was the frequent breakage of products during shipment to customers or inside the production floor. This could be due to ineffective packaging schemes, absence of selection criteria for subcontractors and forwarders or lack of material handling equipment. Conclusively, recommendations were formulated to address the issues that earlier identified and present to the company opportunities for sales growth. Business tools such as GE's Strategic Business-planning Grid and Product / Market Expansion Grid was presented to assist the company in formulating its goals over the long term. CMII can tap local markets as well as other foreign countries like Japan and France as they have a consistently increasing demand for decorative items. There is a need to have an extensive marketing campaign that would at first incur significant costs but would prove to be a fruitful investment in the future. At the operational level, utilization of hand pallet trucks could help increase productivity as well as decrease material handling by workers, which can often lead to breakage of products. A vital element in CMI is the presence of subcontractors. These products designed by CMI but outsourced, represent the company to its consumers. A criteria for evaluating subcontractors was presented to determine which subcontractor would best fit a particular order based on the specifications of the buyer. In addition, a criteria for the selection of suppliers was also suggested in order to assess the reliability of the forwarders in shipping the goods to the company's customers. Finally, in implementing these changes, a period of six months is given for assessing the current system of the company, three months for the review of recommended solutions and a trial duration of 16 months for the execution of approved proposals. Areas for further study included a performance of cost accounting procedures (e.g. cost ? benefit analysis) in the company's every transaction.